Effect of Moringa oleifera Leaves Powder (Sahajjan) on Physiochemical Properties of Chicken Bhujia - Masar, Priyanka; Berwal, Raj Kumar; Meena, Priyanka; Tanwar, Anita; Godara, Kapil Kumar; Choudhary, Vimala; Kumar, Sandeep; Kumari, Saroj; Kalla, Yamini; Parerna (International Journal of Bio-resource and Stress Management, 2025)
The experiment was conducted during January–December, 2024 at the Dept. of Livestock Products Technology, College of Veterinary and Animal Science, RAJUVAS, Bikaner, Rajasthan, India to study the effect of Moringa oleifera leaf powder on shelf life and physico-chemical properties of chicken bhujia, Chicken, which contributes 48.96% to global meat production, is highly valued for its affordability and health benefits. However, processed chicken products are particularly susceptible to lipid peroxidation due to the conditions involved in their processing. While synthetic antioxidants have been traditionally used to prevent oxidation, concerns about their genotoxic effects have led to a growing interest in natural antioxidants derived from polyphenolic compound rich plant sources. This study aimed to evaluate the potential of Moringa oleifera leaf powder (MoLP) as a natural preservative to enhance the storage stability of chicken bhujia (MoLP) was incorporated at levels of 1.5% (T1), 3% (T2) and 4.5% (T3), alongside control samples. The chemicals in moringa serve as potent antioxidants and growth inhibitors for bacteria and fungi. Phenolic chemicals, which are abundant in Moringa, have been shown to significantly reduce food oxidation The chicken bhujia formulated with 3% (MoLP) (T2), which received the highest sensory scores were subjected to further analysis for pH, TBARS, tyrosine, free fatty acid characteristics during ambient temperature storage. The findings revealed that (MoLP) significantly improved the quality of chicken bhujia. It reduced pH, TBARS values, tyrosine value and free fatty acid value.